2013
DOI: 10.1038/nnano.2013.160
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical patterns of three-dimensional block-copolymer films formed by electrohydrodynamic jet printing and self-assembly

Abstract: Self-assembly of block-copolymers provides a route to the fabrication of small (size, <50 nm) and dense (pitch, <100 nm) features with an accuracy that approaches even the demanding specifications for nanomanufacturing set by the semiconductor industry. A key requirement for practical applications, however, is a rapid, high-resolution method for patterning block-copolymers with different molecular weights and compositions across a wafer surface, with complex geometries and diverse feature sizes. Here we demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
136
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(142 citation statements)
references
References 36 publications
3
136
0
1
Order By: Relevance
“…Electrohydrodynamic printing is the highresolution printing analog to IJP. With this method, researchers have achieved nm-scale resolution and achieve this by changes in voltage potentials between the printer nozzle and the surface to be printed on [53,54]. While these methods have shown that they can impact future RF systems, there has not been widespread adoption of these techniques to date making a path towards realization of high performance RF components difficult.…”
Section: Emerging Methodsmentioning
confidence: 99%
“…Electrohydrodynamic printing is the highresolution printing analog to IJP. With this method, researchers have achieved nm-scale resolution and achieve this by changes in voltage potentials between the printer nozzle and the surface to be printed on [53,54]. While these methods have shown that they can impact future RF systems, there has not been widespread adoption of these techniques to date making a path towards realization of high performance RF components difficult.…”
Section: Emerging Methodsmentioning
confidence: 99%
“…Nealey and coworkers have shown a top-down method to create small periodic PS brush nanopatterns on a substrate by a lithographic processes including advanced lithography and O2 plasma etching [111][112][113]. A typical process involves spin-coating a photoresist on a PS brush grafted silicon substrate through "grafting-to", followed by patterning using E-beam lithography to produce line/space and dot arrays.…”
Section: Micro-and Nano-patterned Brushesmentioning
confidence: 99%
“…74 The writing speed is unparalleled when compared to other additive manufacturing technologies presented here (see Table I) and is comparable to the writing speed of EBL. Additionally EHD is capable of printing in three dimensions 73 and because the material is deposited through a solvent, a wide range of materials can be available.…”
Section: Discussionmentioning
confidence: 61%
“…The flexibility of EHD jet printing allows a desirable mixing of block-copolymers with different molecular weight and the material waste of the relatively expensive polymers is greatly reduced. In this way periodic structures with length scales ranging from centimetres to ≈10 nm can be fabricated 74 within the geometrical limitations of block-copolymer self-assembly. Electrospinning from the stable jet mode is used for fast deposition of organic and polymer fibres for applications in nanowire electronic devices, physical biomimetic structures, and field-effect transistors.…”
Section: Electrohydrodynamic Jet Printingmentioning
confidence: 99%